2019
DOI: 10.1039/c9cy01195a
|View full text |Cite
|
Sign up to set email alerts
|

Structure and surface characteristics of Fe-promoted Ni/Al2O3 catalysts for hydrogenation of 1,4-butynediol to 1,4-butenediol in a slurry-bed reactor

Abstract: Nanostructured Ni–xFe/Al2O3 catalysts prepared by sol–gel combustion synthesis (SGC) display superior activity in hydrogenation of 1,4-butynediol to 1,4-butenediol. The Fe addition promoted the Ni reducibility and stabilized the Al2O3 structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…The effects of Ce, Ag, Mo, Fe, and Co, on the textural characteristic of Ni/Al 2 O 3 catalysts are studied by using the nitrogen adsorption/desorption technique (Figure ). According to the classification of IUPAC, nitrogen isotherms of all the samples exhibit type IV isotherms . The nitrogen adsorption‐desorption isotherms of all samples exhibit a comparable H2 hysteresis loop with a saturated adsorption platform, which reflects the relatively uniform distribution of pore diameter and existence of mesopores.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The effects of Ce, Ag, Mo, Fe, and Co, on the textural characteristic of Ni/Al 2 O 3 catalysts are studied by using the nitrogen adsorption/desorption technique (Figure ). According to the classification of IUPAC, nitrogen isotherms of all the samples exhibit type IV isotherms . The nitrogen adsorption‐desorption isotherms of all samples exhibit a comparable H2 hysteresis loop with a saturated adsorption platform, which reflects the relatively uniform distribution of pore diameter and existence of mesopores.…”
Section: Resultsmentioning
confidence: 92%
“…The as‐prepared Ni−M/Al 2 O 3 displays the diffraction peaks at 37.2°, 43.3°, 62.9° and 76.9°, which could be assigned to the NiO (JPCDS 73‐1519). Additional diffraction peaks at 45.0° and 65.6° are indexed to the spinel NiAl 2 O 4 (JCPDS 10‐0339) . It could be observed that the intensity of NiO peaks weakens after the introduction of promoters, indicating the presence of interactions between promoters and nickel or the increased coverage of crystallites of the promoters species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations